Pengaruh belanja modal dan investasi swasta terhadap pertumbuhan ekonomi - Hasanudin Nor; Muhammad Saleh Mire; Rachmad Budi Suharto (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
The purpose of this study is to analyze whether capital expenditure has a significant effect on economic growth and To analyze whether private investment has a significant effect on economic growth in Samarinda City. In this analysis using secondary data obtained from offices and related agencies, among others, obtained through the Central Bureau of Statistics of East Kalimantan Province. With analytical tools used Simple Linear Regression assisted Statistical Program and Service Solution Program (SPSS) version 21.0 for windows. Based on the results of research that capital expenditure has effect on economic growth. And private investment has no effect on economic growth. This means that any changes that occur in capital spending and private investment will not affect anything on economic growth in the city of Samarinda.